Innovations in the Development of Environmental Care Character of Vocational High School in the 21st Century - Syahriani, Fadilla; Ananda, Azwar; Montessori, Maria; Heldi, Heldi; Yufriadi, Ferdi (Journal of Vocational Education Studies, 2024)
This research explores groundbreaking innovations in fostering environmental stewardship within school institutions during the 21st century. In today's world, there is an increasing global emphasis on sustainable living and environmental stewardship, which necessitates the integration of these values into the educational structure, especially at the primary level. By examining various pedagogical strategies, curriculum enhancements, and community engagement initiatives undertaken by educators in Vocational High Schools (SMK), particularly SMK Negeri 1 Ampek Angkek, this study aims to foster a deep sense of environmental responsibility among students. Through a comprehensive review of contemporary practices, this research aims to identify successful models and best practices that contribute to effective environmental character development. The findings from this study not only offer valuable insights for educators and administrators at SMK Negeri 1 Ampek Angkek, but also contribute to a broader discussion on the integration of environmental education into the primary and religious education systems in the 21st century. Ultimately, this exploration serves as a catalyst for advancing environmental literacy and advocacy within educational settings, empowering students to become conscientious stewards capable of addressing the ecological challenges of our time. By nurturing a generation of environmentally conscious individuals, educational institutions can play a pivotal role in fostering a sustainable future for all.